2020
DOI: 10.1038/s41598-020-66154-y
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Cerebrospinal Fluid Biomarkers and Age-related Brain Changes in Patients with Normal Pressure Hydrocephalus

Abstract: Our study aimed to: 1)investigate the diagnostic utility of CSF Aβ42, t-tau, and p-tau to differentiate normal-pressure-hydrocephalus(NPH) from Alzheimer's-disease(AD) and normal-controls; and 2) investigate if age and ventricular size affect the levels of CSF biomarkers in NPH patients. We recruited 131 participants: (a)Suspected-NPH: 72 with ventriculomegaly and clinical symptoms of NPH. These participants were then divided into two groups of 1)Probable-NPH (N = 38) and 2)Unlikely-NPH (n = 34) based on wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
4
10
1
Order By: Relevance
“…Our first result confirmed that patients with iNPH have CSF Aβ 42 concentrations comparable to AD and lower concentrations of p-tau and t-tau than AD, as widely described in previous studies [ 21 , 40 , 41 , 42 ]. In more detail, about 70% of patients in our series had positive CSF Aβ 42 , while p-tau and t-tau were positive in 7% and 11% of patients, respectively, which is consistent with a previous report by Santangelo et al [ 21 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our first result confirmed that patients with iNPH have CSF Aβ 42 concentrations comparable to AD and lower concentrations of p-tau and t-tau than AD, as widely described in previous studies [ 21 , 40 , 41 , 42 ]. In more detail, about 70% of patients in our series had positive CSF Aβ 42 , while p-tau and t-tau were positive in 7% and 11% of patients, respectively, which is consistent with a previous report by Santangelo et al [ 21 ].…”
Section: Discussionsupporting
confidence: 90%
“…A recent study was also not able to validate the usefulness of Aβ 1-42 to differentiate iNPH from AD. 21 Using conservative improvement criteria, our study extends these findings in a large cohort by showing that elevated baseline levels of pTau181 were associated with poor long-term improvement after shunt surgery. Conversely, pTau181 only modestly predicted immediate improvement after TT.…”
Section: Discussionsupporting
confidence: 68%
“…There was no association between age and CSF Aβ42 concentration (r = − 0.322 p = 0.179) or CSF GFAP concentration (r = − 0.167, p = 0.693). Previous studies have not found a correlation between age and Aβ42 concentration in healthy individuals [4951], but regarding GFAP a significant positive correlation between age and protein concentration has been noted in healthy individuals [48].…”
Section: Resultsmentioning
confidence: 99%